Pengembangan Al-Ghazali’s Sufism Happiness Inventory (ASHI):Sebuah Pengukuran Kebahagiaan Sufi - Arman Marwing (TSAQAFAH, 2018)
Happiness is the universal concept that is widely studied in psychology based on the perspective and value of Western society by using a variety of selfreport methods. But, there is still a limited number of research trying to present and develop the concept of happiness of Eastern society who are noted with spiritual aspects, particulary the sufis. This article is a study about Al-Ghazali’s Sufism Happiness Inventory (ASHI), which is a measure of valid and reliable happiness for Sufis aged 20-60 years. It was piloted project and developed to measure four happiness aspects i.e. consciousness of self, consciousness of Allah, consciousness of the world, and consciousness of the hereafter. The result of validity test obtained by 30 respondents confirmed ASHI’s poin validity and r value (Corrected Item-Total Correlation) was 0,361-0,646 with 27 valid items. Futhermore, The Cronbach’s Alpha coefficient was 0,837, which confirmed the scale’s internal consistency reliability. Therefore, ASHI could be used to measure the effect of psychoterapy and its influence to happiness of sufi.